Связь между параметрами электромагнитных, принципиальных схем и схем замещения двухобмоточных трансформаторов - Пентегов, И.В.; Рымар, С.В.; Волков, И.В. (Електротехніка і електромеханіка, 2006)
Отримано рівняння зв'язку між параметрами електромагнітних, принципових і схем заміщення двохобмоткових трансформаторів, що дозволяють об'єднати різні підходи при розрахунку цих схем. Систематизовано правила розстановки знаків у рівняннях трансформатора. Получены уравнения связи между параметрами электромагнитных, принципиальных и схем замещения двухобмоточных трансформаторов, которые позволяют объединить различные подходы при расчете этих схем. Систематизированы правила расстановки знаков в уравнениях трансформатора. Equations of relation between all parameters of electromagnetic and schematic circuits (two magnetically coupled circuits) and galvanically coupled Т- and pi-equivalent circuits without magnetic coupling are deduced for double-winding transformers. This approach can also be applied to double-winding reactors. The obtained formulas facilitate designing of both converting equipment by means of electromagnetic and electrical schematics of transformers and electromagnetic elements through application of transformers' equivalent circuits because they unite different approaches for transformer calculation. Rules of sign arrangement in the equations of transformers are systematized.